2019
DOI: 10.1108/heswbl-09-2018-0088
|View full text |Cite
|
Sign up to set email alerts
|

Effects of work value orientation and academic major satisfaction on career decision-making self-efficacy

Abstract: Purpose An increasing number of students delay graduation or graduate without a job, because they are not ready to make a career decision. In addition, the growing number of young adults who are not in education, employment or training (NEET) has become a social concern in South Korea. To facilitate career decision-making of undergraduates, this study examined the effects of work value orientation and academic major orientation on career decision-making self-efficacy (CDMSE). The purpose of this paper is to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 40 publications
3
22
0
1
Order By: Relevance
“…This evidence is supported by the data from the SEM which shows that WVOs and AMS were significantly contributed to the explanation of the variance in CDMSE. This result is aligned with prior research that suggests WVOs influenced AMS and CDMSE (Doo & Park, 2019). This result is also supported by other previous research findings that work value and major satisfaction of dental hygiene students have a positive effect on CDMSE (Ji & Heo, 2019).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This evidence is supported by the data from the SEM which shows that WVOs and AMS were significantly contributed to the explanation of the variance in CDMSE. This result is aligned with prior research that suggests WVOs influenced AMS and CDMSE (Doo & Park, 2019). This result is also supported by other previous research findings that work value and major satisfaction of dental hygiene students have a positive effect on CDMSE (Ji & Heo, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…According to Masternak and Ross (1992), extrinsic WVO (i.e., focusing on pay and advancement) is an important factor in assessing job attractiveness, indirectly influencing CDMSE. In contrast, Doo and Park (2019) found an insignificant relationship between extrinsic WVO and CDMSE. Several studies have found that extrinsic work values are more stable than intrinsic work values in terms of the stability of work value types (Easterlin & Crimmins, 1991;Jin & Rounds, 2012).…”
Section: Intrinsic and Extrinsic Wvos And Cdmsementioning
confidence: 68%
See 3 more Smart Citations